The effect of marital adjustment on mother-baby bonding and breastfeeding self-efficacy level - Altıparmak, Sümeyye; Yılmaz, Ayşe Nur; Derya, Yeşim Aksoy (My University, 2021)
This study was conducted to determine the effect of marital adjustment on mother-baby bonding and breastfeeding self-efficacy. This cross-sectional study is conductedon 510 postpartum women, who delivered a baby in a public hospital in the eastern region of Turkey, between January and June 2019. Data were collected using PersonalInformation Form, Marital Adjustment Scale (MAS), Mother-Infant Bonding Scale (MIBS) and Breastfeeding Self-Efficacy Scale Short Form (BSES). Data were analyzedby descriptive statistics and t test and Pearson correlation analysis were used in independent groups. The mean age was 29.2 ± 6.67 and it was found that 78.8% ofthe postpartum women had a desired / planned pregnancy, 48.4% breastfed their baby within the first half hour after birth, and 70.2% gave only breast milk within thefirst 24 hours after birth. The mean MAS score was 44.29 ± 8.06; the mean MIBS score was 22.97 ± 2.58; and the mean BSES score was 59.02 ± 9.84. It was found thatpostpartum women with an adjusted marriage relationship (59%) had a statistically higher level of mother-infant bonding and breastfeeding self-efficacy compared topostpartum women with non-adjusted marital relationships (p <0.05). It was found that there was a weak positive correlation between the mean MAS score and the meanMIBS score (r = 0.278, p = 0.000). It was also found that there was a moderate positive correlation between the mean MAS score and the mean BSES score (r = 0.507, p= 0.000). It was found that postpartum women who had an adjusted marital relationship had higher levels of mother-infant bonding and breastfeeding self-efficacy thanthose leading a non-adjusted marital relationship. In addition, it was observed that mother-infant bonding and breastfeeding self-efficacy increased as marital adjustmentincreased in postpartum women.
Keywords: Beslenme ve Diyetetik; Kadın Hastalıkları ve Doğum; Aile Çalışmaları